Keaksaraan Awal Pada Anak Usia Dini: Tinjauan Dari Sudut Pandang Orang Tua Dan Pendidik - Diah Retno Anggraini (UIN Sultan Maulana Hasanudin Banten, 2022)
Early literacy for early childhood continues to invite pros and cons. This is what makes parents and educators a dilemma in this study. The purpose of this study is to provide an overview from the point of view of parents and educators on the problem of early childhood literacy. This study invited 6 parents, 6 educators and 1 psychologist to share their point of view through interviews followed by observation for 6 months. Parents are afraid of their children's reading-writing-counting abilities, that is what drives them to include their children in conventional early literacy learning, while educators mix the concepts of playing and conventional as a result of parental demands. Early literacy is not wrongly given to early childhood, what is wrong is the way it is delivered, conveying it with a fun concept, playing while learning. Because basically, children have the right to enjoy their childhood without having to be snatched away by the anxiety of their parents who are their trusted people.